2019
DOI: 10.1111/ele.13351
|View full text |Cite
|
Sign up to set email alerts
|

A mother’s legacy: the strength of maternal effects in animal populations

Abstract: Although mothers influence the traits of their offspring in many ways beyond the transmission of genes, it remains unclear how important such ‘maternal effects’ are to phenotypic differences among individuals. Synthesizing estimates derived from detailed pedigrees, we evaluated the amount of phenotypic variation determined by maternal effects in animal populations. Maternal effects account for half as much phenotypic variation within populations as do additive genetic effects. Maternal effects most greatly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
145
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 88 publications
(158 reference statements)
16
145
1
Order By: Relevance
“…Maternal effects may translate environmental cues from the mother to the offspring for example via maternally transferred hormones (hereafter 'maternal hormones'), potentially increasing offspring survival in the predicted conditions (adaptive maternal effects, 1,[2][3][4]. Maternal hormone-mediated effects have been recently highlighted as a potential mechanism and source of phenotypic plasticity to respond to changing climate (5)(6)(7), yet empirical evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal effects may translate environmental cues from the mother to the offspring for example via maternally transferred hormones (hereafter 'maternal hormones'), potentially increasing offspring survival in the predicted conditions (adaptive maternal effects, 1,[2][3][4]. Maternal hormone-mediated effects have been recently highlighted as a potential mechanism and source of phenotypic plasticity to respond to changing climate (5)(6)(7), yet empirical evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the observed lower reproductive performance, as measured after one generation of common garden, must originate from persisting intergenerational plasticity rather than from genetic evolution. A recent meta-analysis indeed demonstrated that maternal effects are an influential source of phenotypic variation across the tree of life (Moore, Whiteman and Martin, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal effects are the non-genetic influences of a mother on her progeny and are thought to 36 be adaptive (Moore et al, 2019;Mousseau and Fox, 1998;Yin et al, 2019). Maternal 37 hormones transferred to the next generation are a potential prenatal pathway for mothers to 38 shape their offspring phenotype (Groothuis et al, 2005;Groothuis et al, 2019;Ruuskanen 39 and Hsu, 2018, 20).…”
Section: Introduction 35mentioning
confidence: 99%